The Types of Taur-taur Folk Song in Simalungun Culture - Sitopu, Sapna; Hutajulu, Rithaony; Sholikhah, Rahmatika Luthfiana (Proceeding International Conference on Malay Identity, 2024)
Taur-taur, as a form of vocal art expression of the Simalungun community holding a cultural richness that needs to be preserved. The main focus of this research is on five types of taur-taur, namely Taur taur bahtonang, taur taur simbandar, taur taur Balok ganjang, Taur taur urdo-urdo, and Taur taur tangis-tangis. Each type of taur-taur has unique characteristics whether in terms of melody, lyrics, or social functions within the Simalungun community. Through a qualitative approach, this study finds that taur-taur has distinctive features that set it apart from other forms of folk singing. Musical analysis using Crishty's theory and Merriam's ethnomusicology theory provides a deeper understanding of the vocal techniques and symbolic meanings contained within taur-taur. This research concludes that the preservation of taur-taur is crucial for maintaining Indonesia's cultural diversity. One of the preservation efforts that can be undertaken is to introduce taur-taur to the younger generation through music education.